Pengaruh Parameter Proses 3D Printing Tipe FDM Terhadap Kekasaran Permukaan Produk Menggunakan Filament Acrylonitrile Butadiene Stryene - Pristiansyah; Indun; Hasdiansah; Soni Afriansyah; Ilham Nur Dimas Yahya; Ariyanto; Sugianto (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
A recent development in the manufacturing sector is 3D printing technology. through the direct conversion of 3D computer-aided design (CAD) data into a tangible prototype using the concepts of additive manufacturing. The way that 3D printing technology constructs a prototype is layer by layer. Fibrous materials can be printed using fused deposition modeling (FDM) technology, which produces products with precise geometric properties. Using the Taguchi Method L27(33), three variants of the fixed A transparent ABS There were Three process parameters employed in the study: Nozzle Temperature, Build Plate Temperature, and Print Speed. Filament with a diameter of 1.75 was also used. This study makes use of an FDM Ender 3 Max 3D printer, which has dimensions of x300mm x300mm x350mm. This study's objective is to. The purpose of this study is to measure the surface roughness.test results. The study's experimental findings indicated that, for specimen 2 trials, the ideal roughness value was an average of 14, with the follow parameters, which include 50% print speed, 85°C for the build plate and 250°C for the nozzle temperature.